GENDER AND AGE SPECIFICS OF CARDIOVASCULAR RISK FACTORS PREVALENCE IN RURAL COMMUNITIES OF KRASNODARSKY KRAI - E. V. Bolotova; I. V. Samorodskaya; I. M. Komissarova (Кардиоваскулярная терапия и профилактика, 2015)
Aim. To evaluate the gender and age specifics of cardiovascular risk factor (RF) prevalence in rural population of grown-up population in Krasnodarsky Krai.Material and methods. The RF of CVD in 600 employee of agriculture economy were analyzed, who were being underwent prophylactic screening. The investigation included: questionnaires (smoking, alcohol, hypodynamia), measurement of blood pressure level, body mass index, abdominal obesity (AO), total cholesterol and blood glucose. The weighing of parameters is done according to RF CVD by age and gender. Results. RF of CVD were found in 87,5% of patients. The first range was obesity or overweight in 62,5%, the second — hypercholesterolemia: 49,0%; 6,1% of men vs. 11,1% of women, the third — arterial hypertension (AH): 44,6%; 48,0% of men vs. 41,7% of women, the fourth — AO: 43,1%; 27,1% of men vs. 56,6% (p<0,001), the fifth — smoking: 33,9%; 51,6% of men vs.19,0% women (p<0,001), the sixth — hypodynamia: 18,0%; 9,5% men vs. 25,2%women(p<0,001).Theprevalenceofobesity,AH,hypercholesterolemia, hyperglycemia increased with the age, but smoking and alcohol consumption — decreased. Smoking, AH (at the age >46 y.o.), alcohol consumption were significantly more prevalent in men; obesity (at the age 46-55 y.o.), AO, hypercholesterolemia (at the age 26-55 y.o.) — in women. Conclusion. The development of regional prevention programs and their implementation must be performed according to age and gender specifics of RF CVD prevalence and be directed to a healthy life style.